The use of slot filter in piezocone tests for site characterization of tropical soils - Mondelli, G.; De Mio, G.; Giacheti, H. L. [UNESP]; Howie, J. A. (IOS Press, 2009)
The use of piezocone tests with a slot filter filled with automotive grease for site characterization of tropical soils is assessed. Laboratory tests using the slot filter filled with automotive grease as well as the conventional porous piezo-element saturated with glycerin were carried out to evaluate the pore pressure (u 2) transducer response. CPTu tests using piezo-elements saturated with glycerin and the slot filter filled with grease were pushed side by side in different research sites in Brazil. Estimates of mechanical and hydraulic soil parameters were made based on pore pressure dissipation curves from using both techniques. Laboratory test results indicate that the pore pressure response using the slot filter with grease was delayed when compared to the piezo-element saturated with glycerin, since grease has a higher viscosity. For tropical soils, the records of u2 in piezocone tests using slot filter with grease presented larger peaks than with porous element saturated with glycerin. Records of u2 using the slot filter above the groundwater table suggest the increase of the degree of saturation in unsaturated zone, where porous filter can be desaturated by suction. The slot filter can be used to help the interpretation of the soil profile with deep groundwater level as well as to help detecting its position for some studied soils. The results shown high repeatability for all study sites. This technique is much easier to handle, especially for tropical soils, where the groundwater table is usually deep and pre-drilling is expensive and time consuming. © 2009 IOS Press.
Keywords: Piezocone; Pore pressure; Saturation; Site characterization; Tropical soils; Deep groundwaters; Degree of saturations; Ground water table; Laboratory test; Piezo elements; Piezocone test; Pore pressure dissipation; Porous elements; Porous filters; Pressure response; Slot filters; Soil parameters; Soil profiles; Study sites; Unsaturated zone; Characterization; Geotechnical engineering; Glycerol; Groundwater; Saturation (materials composition); Soil mechanics; Tropics; Soils